HIGH TEMPERATURE PROCESSING OF FISH SAUSAGE-II.EFFECT OF CERTAIN PRESERVATIVES ON THE SHELF LIFE - VICTOR RAJ, M CROSS; CHANDRASEKHAR, T C (Fishery Technology, 2017)
The effects of preservatives like fat coated sorbic acid (FCSA) and glucono-deltalactone (D-lactone), both separately and in combination, on the shelf life of high temperature (115.6°C for 20 min) processed fish sausage, stored at three different temperatures namely, ambient (28 + 2° C), cooler storage (2+ 2°C) and refrigerator (10+ 2° C)were studied. Whereas the control (without preservative), FCSA, D-lactone and FCSA + D-lactone treated samples could be stored for 9, 9, 11 and 13 days respectively at ambient temperature, those stored at lower temperatures were found to be in acceptable condition for 70, 70, an and 80 days respectively. Organoleptic evaluation of taste, flavour the products carried out by panelists revealed that FCSA and FCSA+ D-lactone treated samples were unacceptable with regard to the taste, flavour and texture. However, the taste :flavour and texture of the control and D-lactone treated samples were in acceptable condition.